2021
DOI: 10.1097/inf.0000000000003213
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Neonates With Blood Stream Infection Due to Listeria monocytogenes

Abstract: Background: Infection due to Listeria monocytogenes (LM) is rare in neonates; thus, its clinical presentation and outcomes are not commonly reported, especially in low-and middle-income countries. In 2017, South Africa had an outbreak due to LM. Objective: To determine demographic characteristics, clinical and laboratory findings and outcomes of all neonates infected with LM during the outbreak period. Methods: This is a retrospective analytic study. Clinical and laboratory records of neonates admitted at Chri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Pneumonia was very common and was observed in eleven cases (45.8%) in our study. A study in South Africa showed that 33.3% of neonates were diagnosed with congenital pneumonia, 24 but this value was lower than the 66.7% found in our study. Similarly, in the past 40 years, only 16 pneumonia cases have been reported in France, either as isolated case reports or as small groups of two to seven cases.…”
Section: Discussioncontrasting
confidence: 88%
“…Pneumonia was very common and was observed in eleven cases (45.8%) in our study. A study in South Africa showed that 33.3% of neonates were diagnosed with congenital pneumonia, 24 but this value was lower than the 66.7% found in our study. Similarly, in the past 40 years, only 16 pneumonia cases have been reported in France, either as isolated case reports or as small groups of two to seven cases.…”
Section: Discussioncontrasting
confidence: 88%
“…Early-onset neonatal LM meningitis was defined as age at onset within 7 days; whereas, late-onset LM meningitis referred to age at onset between 7 and 28 days ( 21 ). The LM meningitis hospitalization mortality rate was defined as the number of patients who died during hospitalization divided by the total number of patients.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, pregnant women are reporting symptoms such as headaches, chills, dizziness, and gastroenteritis, which can lead to stillbirth, early delivery, abortion, or septicemia in the child [7]. In addition, listeriosis may lead to other fatal conditions, such as encephalitis and rhombencephalitis, and these may result to meningoencephalitis, conjunctivitis, pneumonia, and meningitis, especially in infants [8][9][10].…”
Section: Introductionmentioning
confidence: 99%